Subspecies-level systematics and affinities of Cheimas Thieme—an endemic genus of the subparamo of the Venezuelan Cordillera de Mérida (Lepidoptera: Nymphalidae, Satyrinae) - Pyrcz, Tomasz W.; Lorenc-Brudecka, Jadwiga; Boyer, Pierre; Zubek, Anna (Zootaxa, 2018)
The validity of the monobasic neotropical butterfly genus Cheimas Thieme (Nymphalidae, Satyrinae, Satyrini, Pronophilina) is discussed, and confirmed based on morphological and molecular data. Cheimas opalinus (Staudinger), endemic to the Venezuelan Cordillera de Mérida, and considered prior to this study to be monotypic and restricted to the central part of the range, is demonstrated to be polytypic and more widely distributed. Five subspecies are recognised, differing mostly in their dorsal patterns, in particular the shape and colour of hindwing greenish–blue patch. Mitochondrial DNA sequences (COI) were obtained for three of them. The nominate subspecies is found in the central part of the range, in the Sierra Nevada and La Culata. The other subspecies are found as follows: C. opalinus dominici n. ssp.; in the Santo Domingo valley in the centre-north; C. opalinus cristalinus n. ssp. in the north; C. opalinus iosephi n. ssp. on the eastern slopes, and C. opalinus rosalinus n. ssp. in the southern Páramo El Batallón massif. A hybrid zone between the latter two subspecies was detected in the northern part of the Batallón massif based on unusual individual variation and intermediate phenotypes. All the populations of Cheimas opalinus occur in the forest–paramo ecotone at 2800–3400 m a.s.l., with the notable exception of C. opalinus cristalinus n. ssp. found also in mid-elevation forests down to 2300 m a.s.l.